Prior and Tichý’s Concepts of Temporalism - Zuzana Rybaříková (Organon F, 2023)
At the beginning of modern logic, propositions were defined as unchangeable entities placed in a certain idealistic realm. These unchangeable propositions contain in themselves so-called indexical, i.e. the place, time and other circumstances of the utterance. This concept of the proposition, which is entitled eternalism, was and is still prevalent among analytic philosophers. Often even the term ‘proposition’ is identified with an idealistic entity located outside the real world. In my paper, I would like to focus on the concept of propositions of two logicians who deviated from the standard understanding of propositions, Arthur N. Prior and Pavel Tichý. They were both proponents of temporalism, i.e. the view that propositions could change their truth-value over time. The paper will discuss the reasons why they were proponents of temporalism and compare their views. It claims that in Prior’s case, his metaphysical views were the main reasons he was a proponent of temporalism. In contrast, when Tichý presented his arguments for temporalism, he focused primarily on natural language.